Driving strategic change at the Junior League. (A) - Shumate, Michelle, (SAGE knowledge. Cases., 2016)
'Driving Strategic Change at the Junior League' describes a troubled organizational environment. Challenges included a dissatisfied membership, declining membership numbers, a large diversity among local leagues and limited resources to meet the organization's overall objectives. The case describes a 'participatory roadmap' approach, drawing on the insights of comprehensive research, and highlights a strategic-change approach that focuses on participation and local-level flexibility.